2017
DOI: 10.1177/0271678x17701459
|View full text |Cite
|
Sign up to set email alerts
|

The absence of the CD163 receptor has distinct temporal influences on intracerebral hemorrhage outcomes

Abstract: Hemoglobin (Hb) toxicity precipitates secondary brain damage following intracerebral hemorrhage (ICH). CD163 is an anti-inflammatory Hb scavenger receptor and CD163-positive macrophages/microglia locally accumulate post-bleed, yet no studies have investigated the role of CD163 after ICH. ICH was induced in wildtype and CD163 mice and various anatomical and functional outcomes were assessed. At 3 d, CD163 mice have 43.4 ± 5.0% (p = 0.0002) and 34.8 ± 3.4% (p = 0.0003) less hematoma volume and tissue injury, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 30 publications
(60 reference statements)
1
43
1
Order By: Relevance
“…The prevention of acute changes in vascular smooth muscle we previously reported appeared to be due in part to probable reductions in neuroinflammatory processes (Yang et al, 2016). Further, in CD163−/− mice there was a decreased acute (3 days) inflammatory response to ICH (Leclerc et al, 2018). Similarly, heme oxygenase 1 (HO-1) activation and overexpression in astrocytes improved BBB disruption after ICH, acutely (Chen-Roetling et al, 2015).…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…The prevention of acute changes in vascular smooth muscle we previously reported appeared to be due in part to probable reductions in neuroinflammatory processes (Yang et al, 2016). Further, in CD163−/− mice there was a decreased acute (3 days) inflammatory response to ICH (Leclerc et al, 2018). Similarly, heme oxygenase 1 (HO-1) activation and overexpression in astrocytes improved BBB disruption after ICH, acutely (Chen-Roetling et al, 2015).…”
Section: Discussionmentioning
confidence: 72%
“…Most studies investigating the vascular effects of ICH focused on the components of the neurovascular unit (NVU), endothelia, astrocytes and pericytes, with an eye toward blood brain barrier (BBB) breakdown. The disruption of the BBB by ICH leads to numerous downstream (secondary) events including increased bleeding, neuroinflammation and edema formation (Yang et al, 1994;Chen-Roetling et al, 2015;Leclerc et al, 2018;Xu et al, 2019). An 11% reduction in vessel density and volume was reported adjacent to the ICH lesion using high resolution micro-computed tomography (Xie et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Macrophage M1/M2 polarization have been identified in various central nervous system diseases, such as traumatic brain injury, spinal cord injury, and ischemic stroke [25][26][27]. The activation of macrophages occurs in the hemorrhagic brain and leads to inflammatory damage following ICH [28][29][30]. However, the specific mechanisms underlying macrophage polarization following ICH have not been well studied.…”
Section: Discussionmentioning
confidence: 99%
“…Heme oxygenase-1 (HO-1) is a key enzyme of heme degradation and the haptoglobin/hemoglobin-CD163-HO-1 system represents a basic line of defense against hemoglobin neurotoxicity by facilitating hemoglobin removal (Thomsen et al, 2013 ). We and others have demonstrated that CD163 is expressed and contributes to hematoma clearance following ICH (Cao et al, 2016 ; Liu et al, 2017 ; Leclerc et al, 2018 ), but the functions of CD163 have not been investigated after SAH.…”
Section: Introductionmentioning
confidence: 99%